Inclusion of Twenty-First Century Skills in the Books of Digital Skills for Fourth Elementary School in Saudi Arabia - Alqurini, Haya Ali; Al-Muhammadi, Najwa Atyan (Journal of Educational and Psychological Sciences, 2024)
The study aimed to reveal the degree to which twenty-first century skills are included in digital skills textbooks for the fourth, fifth, and sixth grades of primary school in the Kingdom of Saudi Arabia. To achieve this, the study followed the descriptive analytical method using the content analysis method. The content analysis card was prepared according to the twenty-first century skills as a study tool, and it consisted of three main skills: the learning and innovation skill, the technology, information and media skill, and the life and work skill, under which (39) sub-skills were included. The tool was used after verifying its validity and reliability. The study found that the average degree of inclusion of twenty-first century skills in the content of digital skills books for the primary stage was (23.33%), which is a low degree, and the degrees of inclusion of twenty-first century skills in the content of digital skills books for the primary stage varied between medium and low, so learning and innovation skills came In the first place with a moderate degree of inclusion amounting to (56.69%), followed by technology, information and media skills in the second place with a low degree of inclusion amounting to (22.00%), while in the third and final place were life and work skills with an equally low degree of inclusion amounting to (20.30%), as the results showed. The degree of inclusion of learning and innovation skills in digital skills books, technology, information and media skills, and life and work skills varies according to the fourth, fifth, and sixth grades of primary school. In light of the research results, the researcher recommended a set of recommendations, perhaps the most prominent of which are: Drawing the attention of those concerned with curriculum planning and development to reconsidering the content of the skills books. Digital for primary school.
Keywords: 21st century skills; Learning and innovation skill; technology; information and media skill; life and work skill